Integrating Islamic Eco-Theology into Religious Education: A New Paradigm for Curriculum Development - Mukhsin Mukhsin; Ilzam Hubby Dzikrillah Alfani (ADPISI (Asosiasi Dosen Pendidikan Agama Islam Se-Indonesia), 2025)
The global environmental crisis demands a transformative educational approach, particularly in Islamic Religious Education (IRE), which has traditionally been anthropocentric. This conceptual study proposes a paradigm shift by integrating Islamic eco-theology into IRE curriculum development. Through qualitative analysis, utilizing library research and conceptual analysis of primary Islamic sources and curriculum theory, we construct a framework based on a Theo-Eco-Centric paradigm—positioning the God-human-nature relationship as foundational. The framework aims to cultivate an Eco-Conscious Muslim who internalizes the values of khalifah (stewardship) and amanah (trust) as environmental ethics. This is operationalized through systematic integration across core IRE subjects (Aqidah, Akhlak, Fiqh, History), employing transformative pedagogies like project-based learning and critical eco-theology circles, and authentic assessment via portfolios and scenario-based evaluations. The study concludes that this framework represents a significant reorientation of IRE, empowering it to address contemporary ecological challenges. As a conceptual proposal, it requires future empirical validation. The research contributes to Islamic educational reform and broader interfaith dialogues on sustainability.